Ketika Anak Melukai: Tinjauan Hukum Islam Tentang Tanggungjawab Pidana Anak dalam Kasus Kekerasan: When Children Injures: Islamic Law Perspective on the Criminal Responsibility of Children in Violence Case - Asiyah Jamilah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This research aims to find out how the law is enforced against children who commit violent crimes from the perspective of Islamic law. The research method used in this research is normative research using library study techniques. The results of the research show that in Islamic law, minors who commit criminal acts cannot be sentenced to kisas because they have not yet reached the age of taklif. However, they can be subject to sanctions in the form of ta'zir as a form of warning and education. Criminal responsibility for children is considered incomplete because they do not yet have full legal capacity. Imposing sanctions takes into account aspects of age, psychological, mental, spiritual maturity and the overall welfare of the child.